Pengaruh Stres Kerja dan Happiness At Work terhadap Turnover Intention Karyawan di Pt. Einsteins Bali Group - I Komang Tria Sutawangsa; Ratna Devy Winayanti (Pusat Riset dan Inovasi Nasional, 2026)
Employee turnover is a natural phenomenon in the business world, but a high turnover rate can be an indication of internal company problems. PT. Einsteins Bali Group faces fluctuations in turnover intention every month, which is characterized by an increasing desire of employees to resign. This phenomenon arises due to discomfort at work, a tendency to work stress, and a low level of happiness at work. This study aims to analyze the influence of work stress and happiness at work on employee turnover intention. The research method used a saturated sampling technique with a sample of 38 respondents. Data analysis was carried out through multiple linear regression to determine the relationship and influence of independent variables on dependent variables. The results of the study are expected to provide an empirical picture of the extent to which work stress increases turnover intention, as well as how happiness at work plays a role in reducing this tendency. These findings are expected to be input for company management in designing more effective human resource management strategies, especially in creating a healthy, comfortable, and supportive work environment for employees. Thus, companies can minimize turnover intention and increase workforce retention.